Trade linkages of inward and outward FDI: Evidence from Malaysia - Goh, Soo Khoon; Wong, Koi Nyen *; Tham, Siew Yean (Elsevier, 2013)
Developing and transition economies are an increasingly important source of outward foreign direct investment (OFDI). The objective of this paper is to fill the gap in the literature regarding outward foreign direct investment by adopting the well known gravity model to examine the relationship between trade (export and import), inward and outward FDI using Malaysia as a case. This contributes to the literature as previous studies on OFDI in Malaysia have focused primarily on the determinants of these outward flows, and there are no studies examining the impact of OFDI on trade. Based on Hausman-Taylor estimation method, our findings reveal that inward foreign direct investment (IFDI) conforms to the observed pattern of a complementary relationship between FDI and trade, while OFDI and trade linkages are not significant as OFDI is dominated by the services sector, which generally is non-tradable. However, intra-firm trade in services could be increased through the process of fragmentation or outsourcing.